The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12885-022-09216-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of SPI1-TYROBP-FCER1G network in oncogenesis and prognosis of osteosarcoma, and its association with immune infiltration

Abstract: Osteosarcoma is an aggressive malignant bone sarcoma worldwide. A causal gene network with specific functions underlying both the development and progression of OS was still unclear. Here we firstly identified the differentially expressed genes (DEGs) between control and OS samples, and then defined the hub genes and top clusters in the protein–protein interaction (PPI) network of these DEGs. By focusing on the hub gene TYROBP in the top 1 cluster, a conserved TYROBP co-expression network was identified. Then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…This protein functions in signal transduction, bone modeling, brain myelination, and inflammation by binding to zeta chain-associated protein kinase 70 kDa (ZAP-70) and spleen tyrosine kinase. [ 11 ] TYROBP is a regulatory protein of various activated receptors in natural killer cells, which activates small colloidal cells to recognize and phagocytose glioma cells. [ 12 ] TYROBP can mediate natural killer (NK) cell activation with NK cell receptors such as KIR2DS2 and KLRD1/KLRC2 heterodimer and promote NK cell receptors KIR2DS1 and KIR2DS2 and KIR2DS4, and ensure its stability on the cell surface, enhance and maintain the cytotoxic effect of NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…This protein functions in signal transduction, bone modeling, brain myelination, and inflammation by binding to zeta chain-associated protein kinase 70 kDa (ZAP-70) and spleen tyrosine kinase. [ 11 ] TYROBP is a regulatory protein of various activated receptors in natural killer cells, which activates small colloidal cells to recognize and phagocytose glioma cells. [ 12 ] TYROBP can mediate natural killer (NK) cell activation with NK cell receptors such as KIR2DS2 and KLRD1/KLRC2 heterodimer and promote NK cell receptors KIR2DS1 and KIR2DS2 and KIR2DS4, and ensure its stability on the cell surface, enhance and maintain the cytotoxic effect of NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…MEG3 and SIP1 exert regulatory effects on various tumors via mechanisms involving tumor macrophage aggregation and polarization, immune infiltration, chemotherapy sensitivity, PTEN, CCL7 transcription, and p53 signaling pathways [ [36] , [37] , [38] , [39] , [40] ]. One study on the role of the SPI1-TYROBP-FCER1G network in osteosarcoma occurrence and prognosis and its relationship with immune infiltration integrated the GEO database [ 41 ]. However, the associations between MEG3 and TREM2, HCST, TYROBP, and between SIP1 and TREM2 and HCST have not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…SPI1 can be a prognostic marker and immunotherapeutic target for gastric cancer patients [ 35 ]. Li et al found that SPI1 is associated with immune infiltration during oncogenesis [ 13 ]. However, the role of SPI1 in ccRCC is unknown, and the relationship between SPI1 and immune infiltrates in ccRCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional activation of SPI1 can enhance the tumorigenic potential of cervical cancer cells through its effect on PARP9 [ 12 ]. Importantly, Li et al demonstrated that the transcription factor SPI1 can promote the expression of CD86, CCL4/CXCL10/CX3CL1, and MHC-II, thereby increasing immune infiltration [ 13 ]. However, the relationship between of SPI1 expression and immune cell infiltration in ccRCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%